Employ of Citrus By-product as Fat Replacer Ingredient for Bakery Confectionery Products - Caggia, Cinzia; Palmeri, Rosa; Russo, Nunziatina; Timpone, Rosario; Randazzo, Cinzia L.; Todaro, Aldo; Barbagallo, Salvatore (Frontiers in Nutrition, 2020)
Citrus fruits processing is one of the foremost industrial activities in Sicily and the main residual by-product consists in peels and seeds (known as ‘pastazzo’). Traditionally this by-product has been used for different purposes, and only most recently, it has been described as source of a wide range of healthy bioactive compounds and dietary fibers. In the present work, a debittered food grade orange fiber (DOF), extracted from orange juice by-product, was experimentally obtained and tested as fat-replacer at different percentages (30, 50 and 70%) in bakery confectionery products (brioches). The DOF showed high total fiber content, low water activity and a high water binding capacity. The obtained bakery products were characterized for nutritional, technological and microbiological parameters through storage at room temperature. Results highlighted that the addition of DOF results in final products with increased moisture content, mainly after one day of storage, and good textural proprieties. Furthermore, the fat-replacing strategy, at different levels of DOF, resulted in final products with, besides a constant content of carbohydrates, showed lowered fat content, increased content of dietary fiber and protein. In particular, the 50% fat replacement allowed to obtain brioches with improved technological properties and with desirable microbiological traits, mostly within the first 24 hours from production and up to five days of storage.